Causes and Solutions of Construction Crane Accidents in Malaysian Construction Industry - Kong, Sio Kah; Ku, Ze Fung (INTI International University, 2022)
Construction industries play a significant role in contributing to the economic growth of a country. It provides job opportunities to all parties involved in the construction and operation of the building. However, it has one of the highest fatalities and injuries rate among the main economic sectors in Malaysia. This is because all processes in a construction project is extremely hazardous especially projects involving construction cranes. The aim of this study is to determine the causes and solutions of crane accidents in construction industry. The results gathered from the questionnaire shows that the main causes of crane accidents are safety management failure and in-depth training for operators and signalman is the solution for it.